4-(3,5-Dimethyl-1H-pyrazol-1-yl)benzenesulfonamide - Asiri, Abdullah M. (International Union of Crystallography, 2011)
The two aromatic rings of the title compound, C(11)H(13)N(3)O(2)S, are inclined at an angle of 47.81 (4)°. The N atom of the amino unit is pyramidally coordinated; one H atom interacts with the sulfamyl O atom of an adjacent molecule, forming a centrosymmetric hydrogen-bonded dimer. The dimers are linked by N—H⋯N hydrogen bonds, generating a three-dimensional network.